The Students’ Enthusiasm in Learning English of the Tenth Grade Students at SMK Kristen Tagari - Mery Mangin Borong (Teaching English as a Foreign Language Overseas Journal, 2016)
Obviously the use of students’ enthusiasm in learning English the students is not onlyas studying English for knows ability in learning English, but also as a students’enthusiasm in learning English. Therefore, in this situation the students have to knowthe characteristics of students’ enthusiasm in learning English. The research aims atfinding out The Students’ Enthusiasm in Learning English. The researcher in this studyemployed the qualitative research design. The subjects of this research were students ofthe tenth grade students at SMK Kristen Tagari. The results of the research revealedthat the Students’ Enthusiasm in Learning English of the tenth grade students at SMKKristen Tagari are: class interactive, students constantly to answer questions, studentswill come back, find a student’s strength, students listen during learning, preview thelesson, play in spotlight, working exercise, and feedback from students. The studentscan be active in class specially in learning English.